2019
DOI: 10.1038/s41598-019-46339-w
|View full text |Cite
|
Sign up to set email alerts
|

Improving the management procedures in farms infected with the Porcine Reproductive and Respiratory Syndrome virus using PDP models

Abstract: Pig meat production need to be built up in the future due to the increase of the human population worldwide. To address this challenge, there is plenty of room for improvement in terms of pig production efficiency that could be severely hampered by the presence of diseases. In this sense, Porcine Reproductive and Respiratory Syndrome Virus (PRRSV) is one of the most costly disease present in industrial pork production in Europe and North America. We have developed a model to analyze the effect of different man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 38 publications
0
12
1
2
Order By: Relevance
“…Porcine reproductive and respiratory syndrome virus (PRRSV), swine influenza virus (SIV) and porcine circovirus type 2 virus (PCV2) are the most prevalent viral agents [1][2][3][4][5][6]. On the other hand, many non-infectious predisposing factors are also involved in PRDC, such as poor environmental conditions, density, stressors, season of the year, genetic background and production flow (all-in-all out versus continuous flow) [7][8][9]. As a general approach, preventive medicine programs should be based on applying measures to control PRDC in a cost-effective way, such as improving environmental conditions, decreasing density and stressors, combined with vaccination against the major viral and bacterial infectious etiologic factors [10].…”
Section: Introductionmentioning
confidence: 99%
“…Porcine reproductive and respiratory syndrome virus (PRRSV), swine influenza virus (SIV) and porcine circovirus type 2 virus (PCV2) are the most prevalent viral agents [1][2][3][4][5][6]. On the other hand, many non-infectious predisposing factors are also involved in PRDC, such as poor environmental conditions, density, stressors, season of the year, genetic background and production flow (all-in-all out versus continuous flow) [7][8][9]. As a general approach, preventive medicine programs should be based on applying measures to control PRDC in a cost-effective way, such as improving environmental conditions, decreasing density and stressors, combined with vaccination against the major viral and bacterial infectious etiologic factors [10].…”
Section: Introductionmentioning
confidence: 99%
“…двічі з інтервалом 3 тижні. У разі виникнення хвороби заходи боротьби з мікоплазмозом свиней грунтуються на розриві епізоотичної ланцюга, запобіганні контакту між хворими та здоровими тваринами, поліпшенні умов утримання, годівлі та виключення стресових чинників, що знижують резистентність організму (Colomer, Margalida, & Fraile, 2019;Nathues et. al., 2013).…”
Section: актуальність темиunclassified
“…Several studies have documented that the type of farm management practices and antibiotic use affect the incidence of swine respiratory diseases, including Glässer's disease [20][21][22]. For instance, Hurnik et al [23] reported several risk factors in the epidemiology of enzootic pneumonia such as feeding methods, housing type, farm size and management practices.…”
Section: Introductionmentioning
confidence: 99%